Pengaruh Company Growth, Komite Audit, Komisaris Independen, Cash Flow, dan Dividend Payout Ratio Terhadap Konservatisme Akuntansi - Lielin Nidya Alvira; Eny Kusumawati (Economic Reviews Journal, 2024)
Conservatism is the principle of prudence in financial reporting where companies do not immediately recognize and measure asets and profits but immediately recognize losses and debts that may occur. This study aims to analyze the effect of company growth, audit committee, independen commissioners, cash flow, dividend payout ratio on accounting conservatism in non-financial companies listed on the Indonesian stock exchange for the period 2020-2022. The sampling technique used in this study was purposive sampling. A total of 273 companies that have met the criteria as observation units. The analysis method used is multiple linear regression analysis. The results of the study provide empirical evidence that the audit committee, independen commissioners, and dividend payout ratio affect accounting conservatism. While company growth and cash flow have no effect on accounting conservatism.